Workshop Pengembangan Bisnis Melalui Media Elektronik Berbasis Sosio-Technopreneur Terhadap Usaha Desa Dengan Produk Es Cream Desa Wilayut - Abdul Hafidz Rosydi Fuady; Amaris Evania Putri; Laila Badriyah; Eli Masnawati; Eli Retnowati; Didit Darmawan; Rahayu Mardikaningsih (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
The objectives of this community service (PKM) are (1) Increasing the entrepreneurial capacity building of UPPKA Kelut Makmur (Klagen-Wilayut Makmur) cadres in Wilayut Village, (2) UPPKA Kelut Makmur cadres have the provision of soft skills and hard skills to carry out businesses with competitive advantages, (3) Ice Cream Products "Food Healty" can be developed for business. The target is 15 UPPKA Kelut Makmur cadres who are members who manage village businesses. The problems faced are: a. Do not have capacity building as a provision for the ability to do business; b. Limited facilities and infrastructure; d. Lack of product creativity; e. Lack of product creativity. Lack of product creativity; e. Competence of managers who are still conventional; f. Do not have an integrated business model. Not having an integrated business model. The solution to the problem is an entrepreneurship training programme, through the concept of creative business through electronic media based on socio-technopreneurship. The ice cream business will be developed to be distributed to toddler and elderly posyandu and general customers. The programmes carried out are: conducting a business development programme workshop. The results of PkM are improving soft skills and hard skills of UPPKA Kelut Makmur members as novice business people.